105k views
3 votes
If f(x)=x/3 and g(x)=6x+9 which is equal to f(g(x))

1 Answer

4 votes

Answer:

f(g(x)) = 2x + 3

Explanation:

f(g(x)) is called a composite function

To compute f(g(x)) simply substitute whatever g(x) definition is wherever there is an x in f(x)

We have
g(x) = 6x + 9


f(x) = (x)/( 3)

So instead of x just use 6x + 9 to get


f(g(x)) = (6x+9)/(3) = 2x + 3

User Alyson
by
4.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.